Validation of the ghost shrimp species Neocallichirus pinheiroi Hernáez, Windsor, Paula & Santana (Decapoda: Callianassidae) from the southwestern Atlantic - Hernáez, Patricio; Windsor, Amanda M.; Paula, Caio Augusto; Santana, William (Zootaxa, 2021)
Hernáez et al. (2020) described a new species of ghost shrimp, Neocallichirus pinheiroi, from northeastern coast of Brazil, Western Atlantic. Although the description and figures presented by Hernáez et al. (2020) fully characterize the new species, the journal issue in which the description appeared was published online only, and the article in which N. pinheiroi appeared did not include a ZooBank registration number (LISD), required for validation of new names in electronic-only publications [vide Art. 8.5.3 of the amended Code of the International Commission on Zoological Nomenclature (ICZN, 1999, 2012)]. As result, the name Neocallichirus pinheiroi Hernáez, Windsor, Paula & Santana, 2020, is not available according the International Code of Zoological Nomenclature (ICZN, 1999, 2012). Therefore, the present note serves to validate the name Neocallichirus pinheiroi by fulfilling the ICZN conditions for nomenclatural availability.